The Role of Smallholder Farms in Food and Nutrition Security - Gomez y Paloma, Sergio; Riesgo, Laura; Louhichi, Kamel; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2020)
This open access book discusses the current role of smallholders in connection with food security and poverty reduction in developing countries. It addresses the opportunities they enjoy, and the constraints they face, by analysing the availability, access to and utilization of production factors. Due to the relevance of smallholder farms, enhancing their production capacities and economic and social resilience could produce positive impacts on food security and nutrition at a number of levels. In addition to the role of small farmers as food suppliers, the book considers their role as consumers and their level of nutrition security. It investigates the link between agriculture and nutrition in order to better understand how agriculture affects human health and dietary patterns. Given the importance of smallholdings, strategies to increase their productivity are essential to improving food and nutrition security, as well as food diversity.
Introduction -- PART 1: WHY SMALLHOLDERS REMAIN KEY FOR FOOD AND NUTRITION SECURITY? -- The Role of Smallholder Farms in a Changing World -- Importance of Smallholder Farms as a Relevant Strategy to Increase Food Security -- Rural development strategies and Africa$1 (Bs small farms -- PART 2: HOW TO SUPPORT AND PROVIDE OPORTUNITIES TO SMALLHOLDERS? -- Inorganic Fertiliser use among smallholder farmers in Sub-Saharan Africa: Implications for input subsidy policies -- Global change and investments in smallholder irrigation for food and nutrition security in sub-Saharan Africa -- Smallholder farmers$1 (Baccess to inputs and finance in Africa -- Policies for Improved Food Security: The Roles of Land Tenure Policies and Land Markets -- PART 3: REVISITING THE CONTRIBUTION OF AGRICULTURE TO NUTRITION SECURITY -- Transforming smallholder agriculture to achieve the SDGs -- Impact of Casual and Permanent Off-Farm Activities on Food Security: The Case of India -- The Superior Role of Agricultural Growth in ReducingChild Stunting: An Instrumental Variables Approach -- Conclusions.s
Keywords: Agriculture -- Economic aspects; Development economics; Agriculture; Food science; Agricultural Economics; Development Economics; Agriculture; Food Science